INFLUENCE OF PERCEIVED VALUE AND ATTITUDE TOWARD CONSUMER PURCHASE INTENTION TO BILLY COFFE HOUSE CUSTOMER AT MEGA SMART AREA MANADO - Ondang, Jessica Patrisia (Sam Ratulangi University, 2015)
ABSTRACT Drinks industry in Indonesia is growing rapidly. Cafés/bars or coffee house industries continued to expand by opening more new outlets towards the end of the review period. Purpose of this study are to determine the influence of Perceived Value And Attitudes Toward Consumer Purchase Intention to Billy Coffe House customer at Mega Smart area Manado. This research has conducted on June 2015. The results shows perceived value and attitude has a positive and significant influence on purchase intention on Billy Coffee House at Mega Smart Area in Manado City. Attitude has the first dominant variable that impact to purchase intention. Perceived value has the second dominant variable that impact to purchase intention. Suggestions, Billy Coffee House must improve the marketing strategy faced coffee house competition in Manado City. Billy Coffee House in Mega Smart Manado must focus on internal customer to increase purchase intention in Billy Coffee House business. Keywords: perceived value, attitude, purchase intention Â